Measurement and Evaluation of Cam Chain Noise and Vibration of Motorcycle Engine - Singh, Dalveer (My University, 2014)
Majority of motor cycle engine suffer from problem of noise and vibration after running for few thousands kilometers. This work is based on measuring noise and vibration of timing system of motor cycle engine by separating it from rest of engine parts. 1/1 Octave band analysis at different conditions of rpm, lubrication and chain wear was studied.
ME, MED, Dissertation
Keywords: Cam Chain Noise; Frequency Analysis; Vibration Trouble Shooting; mechanical engineering